On the secondary settler Models robustness by simulation - Espírito Santo, I. A. C. P. (2006)
The aim of this paper is to assess the goodness of the solutions obtained when minimizing the investment and operation costs of a wastewater treatment plant considering three secondary settler models. The obtained optimal designs are introduced in the GPS-X simulator and stress conditions are imposed in order to evaluate the robustness of the solutions. Only the model that combines the ATV design procedure with the double exponential model is able to support the imposed adverse conditions in the sense that the quality of the treated effluent is not compromised.